(untitled) (Bangladesh Journal of Public Administration, 2021)
The case study is lilnited to two carpet factories established under the public sector in 1980, namely, Baghdad-Dhaka Carpet Factory (BDCF) and Furat Kan aphuliC arpet Factory (FKCF). It describes the background leading to the setring-up of the mills and their operational experience in the field of production, marketing and finance. Problems faced in each of these fields have been highlighted while noting BJMC’s attempts at resolving these. The paper ends with a survey of the current management dilemma as to how to ensure profitability of the two carpet factories. A few steps have been suggested which may be considered for evolving a rescue package for the sick industry.